Illegal Logging, Fishing, and Wildlife Trade : The Costs and How to Combat it - World Bank (World Bank, Washington, DC, 2019)
This paper has two goals - to motivate policy makers in developed and emerging economies to pay more attention to illegal logging, fishing, and wildlife trade, and to provide a road map to address the root causes of the illegal activities. Illegal wildlife trade directly causes declines in species population, resulting in the deterioration of ecosystem functions. Illegal activities involve trade of species threatened with extinction, including many keystone species. It also covers a range of mammals, such as pangolins (considered the world’s most trafficked mammal), and wood products such as rosewood, and marine mammals such as the vaquita found in the Sea of Cortez in Mexico. For all practical purposes, combating illegal logging, fishing, and wildlife trade is a governance issue that first and foremost requires high-level political commitment at the national and international levels. The financial action task force (FATF) recommendations (FATF 2012-19) provide a framework for a risk-based, peer-reviewed system of mutual evaluations for compliance with global standards on money laundering and terrorist financing. The national risk assessment tools can be expanded to also address illegal logging, fishing, and wildlife trade and other natural resources crimes.